Changes in the activity of enzymes associated with enzymatic browning and chemical composition during Musa sapientum Linn. 'Kluai Khai' banana fruit ripening - Makboriboon, N.; Teerarak, M.; Saetiew, K. (My University, 2023)
The results showed that the initial firmness of banana fruit harvested at the raw stage was 7 N and decreased to less than 2 N at overripe and very ripe stages. The total soluble solids increased throughout the ripening period, whereas the titratable acidity maintained a high level during the ripening process. The banana peel stayed green during the raw stage, and the yellow color formed between the unripe stage to the overripe stage. The lightness of the banana peel increased from the raw stage to the ripe stage, decreased at the overripe stage, and then dropped sharply at the very ripe stage. This color change was linked to the browning incidence of the fruit peel and an increasing browning area and soluble browning pigment content. The PPO and POD showed a low activity at the raw stage and then increased with advancing ripening and maintained a significantly higher level than the raw fruit. The findings of this study exhibited that the ripening stages of the 'Kluai Khai' banana influence the firmness, peel color, and browning incidence of the fruit peel and the polyphenol oxidase and peroxidase activities.
Keywords: Banana; Browning pigment; Peroxidase; Polyphenol oxidase